National prevalence, trends and outcomes of takotsubo syndrome in hospitalizations with prior history of mediastinal/intrathoracic cancer and radiation therapy. (15th June 2020) - Desai, Rupak; Desai, Aakash; Abbas, Shabber A.; Patel, Upenkumar; Bansod, Snehal; Damarlapally, Nanush; Doshi, Rajkumar; Savani, Sejal; Gangani, Kishorbhai; Sachdeva, Rajesh; Kumar, Gautam
Abstract: Background: Radiation therapy (RT) for cancers in thoracic/mediastinal region has been linked with heart damage following years of radiation exposure. However, prevalence of takotsubo syndrome (TTS) in patients with prior intrathoracic/mediastinal malignancies treated with RT has never been analyzed on a large scale. Methods: We identified adult hospitalizations with prior mediastinal/intrathoracic cancer and RT and TTS using ICD-9 CM codes and the National Inpatient Sample (2007–2014) after excluding current admissions for chemotherapy. We then assessed the prevalence, odds, trends and in-hospital outcomes of TTS-related admissions in patients with vs. without prior intrathoracic cancer and RT. Results: We identified a total of 5, 991, 314 hospitalizations with prior intrathoracic/mediastinal malignancies and RT ( 73 yrs., 85.2% female), of which 7663 (0.13%, 128 per 100, 000) were diagnosed with TTS ( 74 yrs., 95.8% females, 88.1% white). Higher odds and rising trends in TTS per 100, 000 hospitalizations (from 31 to 241) were seen among patients with prior intrathoracic malignancies and RT as compared to those without (from 19 to 104) (ptrend < 0.001). All-cause in-hospital mortality (4.6% vs 2.8%; OR 1.45; 95%CI 1.29–1.63, p < 0.001), cardiogenic shock (4.3% vs 0.2%), cardiac arrest (3.1% vs 0.9%), arrhythmia (34.3% vs 24.6%), stroke (3.6% vs 2.8%), respiratory failure (14.5% vs 4.6%), and median length of stay and hospital charges were significantly higher in the TTS cohort. Conclusions: This study showed higher odds and increasing trends in TTS-related admissions with worse in-hospital outcomes among patients with prior intrathoracic/mediastinal cancer and RT, irrespective of the time interval from cancer diagnosis or RT to TTS occurrence. Highlights: 5, 991, 314 hospitalizations with prior intrathoracic cancer and RT ( 73 yrs., 85.2% female) 7663 (0.13%, 128 per 100, 000) were diagnosed with TTS ( 74 yrs., 95.8% females). Higher odds of TTS among patients with prior intrathoracic cancer and RT Rapidly rising trends in TTS among patients with prior intrathoracic cancer and RT from 2007 to 14 Worse in-hospital outcomes of TTS in patients with prior mediastinal/intrathoracic cancer and RT